Manageable Network Security System Detection Using Mobile Agent - Wawan Indarto (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2005)
Protection of agent data state and partial results in mobile agent systems continues to draw researchinterest. Today hackers disguise their attacks by launching them form a set of compromised hosts distributedacross the Internet. It is very difcult to defend against these attacks or to track down their origin. Commerciallyavailable intrusion detection systems can signal the occurrence of limited known types of attacks. New types ofattacks are launched regularly but these tools are not effective in detecting them. Human experts are still the keytool for identifying, tracking, and disabling new attacks. Often this involves experts from many organizationsworking together to share their observations, hypothesis, and attack signatures..Keyword: agent, intrusion detection, network